Performance Analysis of Friction Stir Welded Lightweight Aluminum Alloy Sheet - Hongfeng Wang; Dunwen Zuo; Shengrong Liu; Jiafei Pu; Weiwei Song (Journal of Engineering and Technological Sciences, 2020)
The present research envisaged the performance analysis of a 1-mm thick 6061-T6 aluminum alloy sheet welded by the friction stir welding technique, using optical microscopy, micro-hardness measurement, a tensile test, a friction and wear test, and a salt spray corrosion test. It was found that the grain in the welded zone obtained was refined under each parameter. When the rotating speed of the tool was 15,000 rpm and the traveling speed of the tool was 300 mm·min-1, the tensile strength of the welded zone was highest, i.e. 74.8% of the base metal. Furthermore, the hardness distribution curve of the welded zone was of the 'W' type under each parameter, but the hardness value was lower than that of the base metal. The friction coefficient of the welded zone was lower than that of the base metal under each parameter, and the wear form was found to be mainly adhesive wear accompanied by abrasive wear. The welded zone and the base metal were subjected to salt spray corrosion after 12 hours under each parameter, which had a negative effect on the quality. However, after 12 hours of subsequent corrosion, the quality of each sample and the base material was not obvious.